Responsibilities of the Board of Commissioners as Tax Bearer for Limited Liability Company Taxpayer - Bustanul Arifin; Rouli Anita Velentina (Faculty of Law, Universitas Pekalongan, 2022)
Tax collection in Indonesia carried out based on the procedures stipulated in the Regulation of the Minister of Finance of the Republic of Indonesia Number 189/PMK.03/2020 concerning Procedures for Implementing Tax Collection on the Amount of Taxes Accrued (“PMK No.189/PMK.03/2020”). In PMK No.189/PMK.03/2020, the Board of Commissioners can be the Tax Bearer of a Limited Liability Company (Perseroan Terbatas “PT”), whereas in Article 32 of Law Number 28 of 2007 concerning General Provisions and Procedures for Taxation, it is not regulated that the Board of Commissioners may become the Tax Bearer. Then, when viewed from Law Number 40 of 2007 concerning Limited Liability Companies as amended by Law Number 11 of 2020 concerning Job Creation, the organ authorized to represent a Limited Liability Company (PT) is the Board of Directors. The problem of this research is how the arrangement of the Board of Commissioners as the Tax Bearer if it is viewed from the applicable laws and regulations. The normative juridical method is the research method used in this research. This research uses secondary data consisting of primary legal sources, secondary legal sources, and tertiary legal sources. From the results of this research, it is concluded that the regulation regarding the responsibilities of the Board of Commissioners in PMK Number 189/PMK.03/2020 is an implementation of Law Number 19 of 1997 concerning Tax Collection with Distress Warrant. In addition, the arrangement is in line with the arrangement of the responsibilities of the Board of Commissioners in the Limited Liability Company Law, as reviewed from Article 69 paragraph (3) jo. Article 114 paragraph (3) of the Limited Liability Company Law which regulates the Board of Commissioners is jointly and severally responsible if the resulting financial statements are incorrect and/or misleading. Nevertheless, the Ministry of Finance is deemed necessary to make some improvements to the deficiencies in the provisions of PMK Number 189/03/2020. Keywords: Board of Commissioners, Tax Law, Tax Bearer, Limited Liability Company, Taxpayer